2006
DOI: 10.1364/ol.31.002118
|View full text |Cite
|
Sign up to set email alerts
|

Fiber-Bragg-grating-assisted surface plasmon-polariton sensor

Abstract: A theoretical scheme for a new surface plasmon-polariton (SPP) fiber sensor with a fiber Bragg grating imprinted into the fiber core for SPP excitation is presented for the first time to our knowledge. In our scheme the energy in the fiber core mode can be transferred to a SPP with high efficiency by means of a properly designed short-period fiber Bragg grating (SPG). Developed for the cylindrical (fiber) geometry, our scheme without loss of generality can be applied to a planar geometry. Our simulations are b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(52 citation statements)
references
References 5 publications
1
51
0
Order By: Relevance
“…The sensitivity of a pure-silica TFT-MG with the diameter of several micrometers is about tens of nm/RIU. By inducing metal-cladding, more cladding modes are possible to be excited and higher sensitivity can be obtained, which is so called grating-assisted surface plasmon-polariton (SPP)-like grating sensor (Nemova & Kashyap, 2006). Figure 16 shows the SEM picture of a metal-dielectric-hybrid TFT-MG (MD-TFT-MG) by FIB milling.…”
Section: Fib Machined Micro-grating For Temperature Sensingmentioning
confidence: 99%
“…The sensitivity of a pure-silica TFT-MG with the diameter of several micrometers is about tens of nm/RIU. By inducing metal-cladding, more cladding modes are possible to be excited and higher sensitivity can be obtained, which is so called grating-assisted surface plasmon-polariton (SPP)-like grating sensor (Nemova & Kashyap, 2006). Figure 16 shows the SEM picture of a metal-dielectric-hybrid TFT-MG (MD-TFT-MG) by FIB milling.…”
Section: Fib Machined Micro-grating For Temperature Sensingmentioning
confidence: 99%
“…In 2006, the authors of this paper suggested an improved sensor by the use the "pure" SPP as opposed to the hybrid mode [20]. Contrary to SPW, in this "pure" SPP, almost all the energy is concentrated at the metal-dielectric interfaces.…”
Section: Guided Wave Surface Plasmon Sensorsmentioning
confidence: 99%
“…Thus, the transmitted signal suffers a change in the amplitude through interference of the guided and cladding modes. The overlap of the excited cladding mode with the SPP is small, as seen in Figure 11: the surface Plasmon hybrid-mode has a substantial amount of its energy associated with the guided mode and is therefore intrinsically less sensitive to the surrounding liquid than the "pure" SPP scheme proposed in [20][21][22][23][24]. The second LPG couples the cladding hybrid mode back into the core mode for direct detection.…”
Section: Guided Wave Surface Plasmon Sensorsmentioning
confidence: 99%
“…Prisms are used in commercial instruments to avoid air-dielectric challenges of getting light into the prism to launch at the SPR angle, θ SPR . Alternative methods include end coupling using various wave guiding configurations [5,6], grating based diffraction assisted angular coupling [7][8][9], optical waveguide coupling [10], multimode optical fiber waveguide coupling [6], single-mode optical fiber waveguide and grating coupling combinations [11][12][13], scattering [14], and many more.…”
Section: Introductionmentioning
confidence: 99%